Building Financial Resilience: How the Accounting Profession Adapts to Technological Change - Priatna Sari, Yeni; Kartika, Dewi; Widianto, Andri; Sawani , Yussri (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
The rapid technological advancement of Artificial Intelligence (AI) has brought challenges across various sectors, including accounting and finance. This study aims to identify and describe the strategic contributions of accountants to the financial system, while also analyzing their level of readiness in adapting to technological change, to explore the factors hindering and supporting accountants in maintaining technology-based financial stability and resilience in the context of Indonesia as a developing country. Using a qualitative descriptive approach, data were collected through a literature review and a survey with the Member of the Indonesian Institute of Accountants (IAI). The findings show that although the level of AI adoption in accounting is still in the early stages, there is a high level of awareness among accountants regarding the urgency of mastering technology. On the other hand, the involvement of regulators and educational institutions still needs to be enhanced to create an ecosystem that supports the technology adaptation among the accountants to support the digital transformation. This study suggests the formulation of adaptive policies, the enhancement of accountants' digital literacy, and the development of AI governance standards as collective efforts to maintain the stability and resilience of the national financial system.